Safety and efficacy of an Anti-CD20 Monoclonal antibody (RedituxTM) In Indian patients with seropositive rheumatoid arthritis - Arun Hegde; Vivek Vasdev; Krishnan Shanmuganandan; Kavita Singh; Sivasami Kartik; Abhishek Kumar (Indian Journal of Rheumatology)
Background: Rituximab (RTX), an anti-CD 20 monoclonal antibody is one of the first line biological disease-modifying anti-rheumatoid drug indicated for the treatment of rheumatoid arthritis (RA) in patient's refractory to conventional Synthetic DMARDs (csDMARDs). Limited data are available about the safety and efficacy of biosimilar version of this molecule. In this study, we assessed the clinical efficacy and safety profile of biosimilar RTX, RedituxTM. Methods: In this prospective study, 36 adults with moderate disease activity measured by the European League Against Rheumatism (EULAR) disease activity score (DAS28-erythrocyte sedimentation rate [ESR] ≥3.2), who had failed conventional therapy with at least 2 csDMARDs were initiated on RTX, 1000 mg, given on day 0 and day 15, after taking informed consent. Biomarkers including ESR, C reactive protein, Immunoglobulin G and M (IgG, IgM) and DAS28-ESR scores were measured at baseline and repeated at 2, 4, 8, 12, 16, 20, and 24 weeks. The primary endpoint was attaining EULAR good/moderate response. Results: DAS28-ESR score showed a statistically significant decline at 24 weeks (P < 0.001). Seventy-five percent patients showed an EULAR moderate response while 25% showed no EULAR response at 24 weeks posttreatment. IgG and IgM levels declined by 24.9% (P < 0.001) and 37% (P = 0.020) at end of 24 wks. However, there were no infections noted during the period of study. The most common adverse event was infusion reaction seen in 16.6% of patients. Conclusions: RTX is a safe and effective drug for the management of seropositive RA with results comparable with the original molecule. No serious adverse effects were noted in the study except for mild infusion reactions and fall in immunoglobulin levels.